2021
DOI: 10.1186/s12301-021-00141-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of scroto-inguinal microsurgical varicocelectomy in treating male infertility

Abstract: Background Varicocele presents as the most frequent cause of infertility in men. Most reports showed that varicocelectomy has a significant impact on male fertility and reproductive outcome. This study aims to evaluate the safety and effectiveness of scrotal–inguinal microsurgical varicocelectomy in treating male infertility. Methods We prospectively studied preoperatively and postoperatively (at 3 and 6 months) 86 consecutive patients diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Following the varicocelectomy procedure, there was a statistically significant increase in the mean total sperm count and the percentage of motile sperm at both the three-month and sixmonth postoperative marks compared to the levels prior to the surgery. Phan et al [27] reported that the first instance of a spontaneous pregnancy in a couple was reported two months after the surgery. Overall, 26.7% [23 out of 86] of all couples had achieved a pregnancy by the end of the follow-up period.…”
Section: Diegidio Et Almentioning
confidence: 99%
“…Following the varicocelectomy procedure, there was a statistically significant increase in the mean total sperm count and the percentage of motile sperm at both the three-month and sixmonth postoperative marks compared to the levels prior to the surgery. Phan et al [27] reported that the first instance of a spontaneous pregnancy in a couple was reported two months after the surgery. Overall, 26.7% [23 out of 86] of all couples had achieved a pregnancy by the end of the follow-up period.…”
Section: Diegidio Et Almentioning
confidence: 99%
“…[ 1 ] The incidence increases by age due to the disruption in blood flow to the testis and likely to cause of infertility in males. [ 2 3 4 ] Surgery is currently considered the gold standard for varicocele therapy and offers a better prognosis when compared with other treatments. [ 5 ] A study by Baazeem et al .…”
Section: Introductionmentioning
confidence: 99%